2018
DOI: 10.1002/asia.201800543
|View full text |Cite
|
Sign up to set email alerts
|

Functional MXene Materials: Progress of Their Applications

Abstract: Nowadays, two-dimensional materials have many applications in materials science. As a novel two-dimensional layered material, MXene possesses distinct structural, electronic, and chemical properties; thus, it has potential applications in many fields, including battery electrodes, energy storage materials, sensors, and catalysts. Up to now, more than 70 MAX phases have been reported. However, in contrast to the variety of MAX phases, the existing MXene family merely includes Ti C, Ti C , (Ti , Nb ) C, (V , Cr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(89 citation statements)
references
References 150 publications
(298 reference statements)
1
88
0
Order By: Relevance
“…Most experimental investigations have mainly focused on the excellent electrochemical behavior of MXenes for energy storage as ion batteries, gas storage, and various catalysis applications because of their large exposed surface area, hydrophilic nature, adsorption ability, and surface activities. The latest applications and developments of MXenes have been summarized in the recent review article [11,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Most experimental investigations have mainly focused on the excellent electrochemical behavior of MXenes for energy storage as ion batteries, gas storage, and various catalysis applications because of their large exposed surface area, hydrophilic nature, adsorption ability, and surface activities. The latest applications and developments of MXenes have been summarized in the recent review article [11,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…MXene, an emerging class of two dimensional transition metal carbides after graphene, exhibits attractive metallic conductivity in virtue of its lamellar electronic transfer channels. [8][9][10][11] Excitingly, MXene, superior to graphene, features an exceptional combination of rich compositions and surface chemistry, surface hydrophilicity, and energy storage functionalities, offering unique advantages for energy-related applications. [12] Among the MXene family, titanium carbide (Ti 3 C 2 T x ) is the most intensively studied and can be used as the host material for LIBs due to its considerable theoretical capacity (320 mAh g À 1 ), lower Li diffusion barrier (0.07 eV), large potential range from ca.…”
Section: Introductionmentioning
confidence: 99%
“…The transition metal MXene has created interests in a conducting guest material to be used in various areas of supercapacitor . The MXenes are a new conducting material with high electrical conductivity (≈9880 S cm −1 ) and hydrophobic surface, which is composed of carbides, nitrides, or carbonitrides . As a capacitor, it has been revealed that the intercalation of cations into layered surface of hydrophilic Ti 3 C 2 MXene provides excellent volumetric capacitance of ≈1500 F cm −3 .…”
Section: Energy Storage Of Cnt Yarnmentioning
confidence: 99%